The representation of historical revisionism as a political propaganda in classical dystopias, 1984 and Fahrenheit 451 - Drohy, Bidita Azad (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2022.